Notes for a Sketch on the History of Women - Fallas Arias, Teresa (2014)
Before approaching the history of women the fact that it was written by men should be considered. It was filled with prejudice, stereotypes and reproduced an androcentric rhetoric which converted the sexual differences of women into inequality and inferiority. In this inquiry the sexual differentiation is valued as complementary and rich as it allows the staging of languages and knowledge previously despised, invisible and annulled during centuries. To think about half of humanity in these times means rejecting the univocal and identical history which hid the experiences of women, to tell them without intermediates and interpreters prone to institutionalized history.